Development and Validation of a Culture-Based Method Suitable for Monitoring Environmental Survival of Escherichia Coli O157:H7 and Salmonella Enterica Serovar Typhimurium in Developing Countries - Ongeng, Duncan; Muyanja, Charles; Ryckeboer, Jaak; Geeraerd, Annemie Helena; Springael, Dirk (Annals of microbiology, 2011)
A non-GMO culture-based method suitable for studying the fate of Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium in an agricultural environment in developing countries was developed and validated. This method is based on the use of spontaneous rifampicin-resistant mutants of non-toxigenic variants of E. coli O157:H7 and S. Typhimurium combined with counting of colony-forming units (CFU) on selective media, i.e., Cefixime–Tellurite–Sorbitol MacConkey agar containing 100 μg/ml rifampicin, 50 μg/ml cycloheximide and 50 μg/ml nystatin for E. coli O157:H7 and Xylose–Lysine–Tergitol-4 agar containing the same antimicrobials for S. Typhimurium. Validation experiments using gfp- and ds-red-labelled derivatives of the rifampicin-resistant mutants in a non-sterile manure-soil matrix demonstrated that the new culture method was effective in the selection and recovery of the test strains without any detectable interference from background contaminants both in the short and long term. The rifampicin-resistant-based culture method designed provides a feasible low-cost option to study environmental survival of E. coli O157:H7 and Salmonella spp. in developing countries.
Keywords: Culture-based method . Rifampicin-resistant . Eschericha coli O157:H7 . Salmonella Typhimurium . Environmental survival . Developing countries